(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the issues of improving the management of higher education institutions in Uzbekistan through digital governance mechanisms. It argues that, under the conditions of rapid digital transformation in the higher education system, there is a growing need to introduce modern management approaches that can enhance the efficiency of administrative processes, ensure greater transparency in decision-making, improve the quality of educational services, and strengthen institutional sustainability. Particular attention is given to the role of digital platforms, automated management systems, data analytics, electronic document flow, and integrated information solutions in the modernization of university administration. The article highlights the organizational and managerial advantages of the digital governance approach, especially in optimizing internal processes, strengthening performance control, increasing the speed of information exchange, and supporting data-driven strategic planning. It also identifies the key barriers to effective digitalization of university management in Uzbekistan, including the insufficient integration of information systems, the limited digital competencies of administrative staff, and the need to improve institutional mechanisms. Based on the findings, the article proposes several directions for enhancing the effectiveness of higher education management through digital mechanisms aimed at sustainable development, greater competitiveness, and alignment with contemporary requirements of the higher education system.